2016
DOI: 10.5606/kbbihtisas.2016.54280
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pneumatized uncinate process and accompanying neighboring variations

Abstract: Objectives: This study aims to investigate the prevalence of uncinate process (UP) pneumatization and also to investigate the association of UP pneumatization with concurrent morphological variations in neighboring structures and the presence of maxillary sinusitis. Patients and Methods:This was a retrospective study where coronal computed tomography scans of 1,500 UPs in 750 patients (483 males, 267 females; mean age 36.3±14.7 years; range 7 to 84 years) were examined to determine the prevalence of UP pneumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The coexistence of UBs and maxillary sinusitis was found to be statistically significant. 25 Our evidence supports the claim that the only type of air cell that can expand into the UP is an LC; UB was found in the present study in 13 (18.05%) of 72 sides. In 750 patients (1500 sides) evaluated by CT, there were UBs found in 6.26% of cases; these were located unilaterally in 1.60% of the patients.…”
Section: The Ub: a Rare Entitysupporting
confidence: 92%
See 2 more Smart Citations
“…The coexistence of UBs and maxillary sinusitis was found to be statistically significant. 25 Our evidence supports the claim that the only type of air cell that can expand into the UP is an LC; UB was found in the present study in 13 (18.05%) of 72 sides. In 750 patients (1500 sides) evaluated by CT, there were UBs found in 6.26% of cases; these were located unilaterally in 1.60% of the patients.…”
Section: The Ub: a Rare Entitysupporting
confidence: 92%
“…In 750 patients (1500 sides) evaluated by CT, there were UBs found in 6.26% of cases; these were located unilaterally in 1.60% of the patients. 25 A different group found UBs in 5% of 512 cases (1024 sides). 24 Kennedy and Zinreich found UB in 1 (0.4%) of 230 patients, on coronal CTs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Variations of uncinate process are clinically crucial because uncinate process is the most important landmark of the lateral nasal wall in endoscopic endonasal operations (Isobe et al, 1998). Uncinate bulla is a rare anatomical variation that obstructs the ethmoid infundibulum when it reaches abnormal dimensions and disrupts sinus ventilation (Kantarci et al, 2004; Yenigun et al, 2016). In the literature, Bolger et al (1991) reported the frequency of uncinate bulla in the individual population is 2.5%; Kantarci et al (2004) 5%, Kaygusuz et al (2014) 6%, Yenigun et al (2016) 6.2%; Dasar and Gokce (2016) found it to be 13.8%.…”
Section: Variations Of Uncinate Processmentioning
confidence: 99%
“…Blumenbach first identified uncinate process in 1790 [1]. It is sickle shaped, sagittally oriented and runs from anterosuperior to posteroinferiorly in the ethmoid labyrinth.…”
Section: Introductionmentioning
confidence: 99%